Evaluating the risk management of electronic banking operations in Libyan banks in light of Basel decisions (مجلة جامعة سرت للعلوم الانسانية, 2024)
Libyan banks are exposed to many banking risks that arose as a result of electronic applications replacing traditional banking operations practices, especially in light of the conditions of political and economic instability that the Libyan state is going through. Given that the success of electronic banking requires following a successful policy to manage the risks associated with it. In 2001, the Basel Committee on International Banking Supervision issued a document for managing the risks of electronic banking operations, which contains sound principles and practices for managing those risks. Therefore, this study aimed to identify the level of commitment of Libyan commercial banks to applying those principles approved by the document. To achieve this goal, the descriptive approach based on the field survey strategy was relied upon, where a field study was conducted on a number of branches of Libyan banks operating in the city of Sirte. The study concluded that: the investigated banks are moderately committed to applying sound practices and procedures - stipulated in the Basel Document - to manage and reduce the risks of electronic banking operations.
Keywords: electronic banking; operations; risks of electronic banking operations